VISITABILITY: A CONCEPTUAL ANALYSIS IN BRIEF - Shehin S; Dr. Riju Saimon (IJRDO - Journal of Social Science and Humanities Research, 2026)
Individuals born with physical disabilities may face a heightened risk of social isolation, both within public and private spheres. This risk may be further exacerbated in the home environment. The literal meaning of the word “visitability” according to the Cambridge English dictionary is something worth visiting or something capable of being visited, enhancing accessibility for everyone (Singh, 2024), irrespective of whether a person with any disability resides in the home. It emphasizes the importance of creating spaces that are inclusive and accessible to all potential visitors by incorporating features that ensure comfort and ease of accessibility (Latika Roy Memorial Foundation, 2024). The concept of visitability, first introduced by Eleanor Smith in 1987 (Smith, 2013), emerged through her advocacy with Concrete Change, an organization dedicated to promoting accessible housing designs. Originally, the criteria for a visitable home included a zero-step entry, a first-floor bathroom, and wheelchair-accessible doorways measuring at least 32 inches wide. Over time, framework of visitability got expanded by incoporating additional features, such as accessible outdoor pathways, first-floor bedrooms, and accessible light switches (National Council on Independent Living., 2024). These design strategies not only accommodate individuals with limited mobility but also enhance the overall functionality of spaces, improving safety and accessibility for tasks such as moving furniture, strollers and large objects.